PENINGKATAN HASIL BELAJAR MATEMATIKA PADA MATERI SIFAT-SIFAT BANGUN DATAR MENGGUNAKAN MEDIA VIDEO PEMBELAJARAN INTERAKTIF DAN GAME EDUKASI WORDWALL DI SD NEGERI LAWANGAN DAYA 2 PAMEKASAN - Novita Sari, Lia; Budiyono, Budiyono; Febriani, Elviera (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The research aims to improve mathematics learning outcomes regarding the properties of flat shapes in class IV of Lawangan Daya 2 Pamekasan Elementary School, which consists of 27 students. The type of research is classroom action research with a quantitative approach using 4 activity stages. The results of this research are: 1) the average class score at the pre-cycle stage is 48 with a completion percentage of 33%; 2) the average class score in cycle 1 increased by 66 with a completion percentage of 63%; 3) the average class score in cycle 2 increased again by 87 with a completion percentage of 96%. Based on the results of the research above, it can be concluded that the use of interactive learning video media and worwall educational games can improve mathematics learning outcomes regarding the properties of flat shapes in class IV at SDN Lawangan Daya 2 Pamekasan.